PSIKOLOGI PENDIDIKAN ISLAM SEBAGAI PENDEKATAN HUMANISTIK DALAM PROSES BELAJAR - Putri Hidayati; Vivik Shofiah (STKIP Subang, 2026)
This study aims to examine Islamic educational psychology as a relevant and comprehensive humanistic approach in the learning process, with a focus on the integration between modern educational psychology theory and Islamic values. The method used is a systematic literature review of 32 academic sources consisting of SINTA-indexed national journals, reputable international journals, and academic books published in the 2014–2024 period. The results of the study indicate that Islamic educational psychology has a humanistic framework that positions humans as whole beings, with cognitive, affective, psychomotor, and spiritual dimensions that are fundamentally different from secular humanism. The learning process in Islam is not solely oriented towards acquiring knowledge, but rather on character formation and achieving sa'adah (true happiness). Teachers in the Islamic tradition play a dual role as murabbi and mu'allim which requires pedagogical competence as well as moral integrity. Learning motivation stems from theological awareness of knowledge as worship, which provides a transcendent dimension beyond conventional extrinsic and intrinsic motivation models. The novelty of this research lies in the systematic mapping of the meeting points between the humanistic dimensions of Islamic psychology and Western educational psychology theories, while also identifying their practical implications for the development of learning models in Indonesian Islamic educational institutions.